Abnormal Properties and Behaviors of Antithrombin III Found in a Thrombophilic Patient: Defective Biological Functions and Dissimilar Antigenic Determinants - Murayama, Hideki; Matsuda, Michio (Thrombosis and Haemostasis, 1986)
Abnormal properties of antithrombin III have been found in a 55-year-old male who has been thrombophilic over the last seven years. They are characterized by 1) defective inhibition of thrombin and activated blood coagulation factor X, 2) reduced affinity to heparin and 3) partial immunological identity with the normal molecule. The antithrombin III molecule, however, preserves a single-chain structure and an apparently identical molecular weight with that of the normal molecule. It is, thus, very unlikely that the impaired functions of antithrombin III in the patient’s plasma are induced by possible proteolytic modifications of the molecule by thrombin or other related activated blood coagulation factors.Since no other members of his immediate family have been found to be affected, the abnormality may be acquired rather than genetically determined, although further investigation is necessary for the elucidation of the abnormality of the molecule.
Keywords: Antithrombin III; Abnormal properties of antithrombin III; Thrombosis; Mesenteric vein thrombosis